Underground Radiobiology: A Perspective at Gran Sasso National Laboratory - Esposito, Giuseppe; Anello, Pasquale; Ampollini, Marco; Bortolin, Emanuela; De Angelis, Cinzia; D'Imperio, Giulia; Dini, Valentina; Nuccetelli, Cristina; Quattrini, Maria Cristina; Tomei, Claudia; Ianni, Aldo; Balata, Marco; et al. (Frontiers in Public Health, 2020)
Scientific community and institutions (e. g., ICRP) consider that the Linear No-Threshold (LNT) model, which extrapolates stochastic risk at low dose/low dose rate from the risk at moderate/high doses, provides a prudent basis for practical purposes of radiological protection. However, biological low dose/dose rate responses that challenge the LNT model have been highlighted and important dowels came from radiobiology studies conducted in Deep Underground Laboratories (DULs). These extreme ultra-low radiation environments are ideal locations to conduct below-background radiobiology experiments, interesting from basic and applied science. The INFN Gran Sasso National Laboratory (LNGS) (Italy) is the site where most of the underground radiobiological data has been collected so far and where the first in vivo underground experiment was carried out using Drosophila melanogaster as model organism. Presently, many DULs around the world have implemented dedicated programs, meetings and proposals. The general message coming from studies conducted in DULs using protozoan, bacteria, mammalian cells and organisms (flies, worms, fishes) is that environmental radiation may trigger biological mechanisms that can increase the capability to cope against stress. However, several issues are still open, among them: the role of the quality of the radiation spectrum in modulating the biological response, the dependence on the biological endpoint and on the model system considered, the overall effect at organism level (detrimental or beneficial). At LNGS, we recently launched the RENOIR experiment aimed at improving knowledge on the environmental radiation spectrum and to investigate the specific role of the gamma component on the biological response of Drosophila melanogaster.